Características físico-químicas, microbiológicas e sensoriais de sucos de uva integral gama irradiados - Mesquita, Taciene Carvalho (2017)
This study aimed at evaluating the effects of gamma irradiation on physicochemical, microbiological and sensory characteristics of grape juice blends during storage at room temperature (21° ± 3°C). Grapes were harvested, cleaned, sanitized and the barries removed. The production of Isabel Precoce x Bordo x BRS Violeta (33% + 33% + 34%) blend was performed by vapor dragging, packed in amber glass bottles and stored at room temperature for 120 days. The gamma irradiation doses applied were 0.0 kGy; 1.0 kGy; 1.5 kGy and 2.0 kGy. The following analyzes were carried out during the storage period: pH, soluble solids (SS), titratable acidity (TA), SS / TA ratio, color (L *, Chroma, ° Hue), total phenolics, antioxidant activity (DPPH and β-Carotene / linoleic acid), total anthocyanins, vitamin C, microbiological and sensory analyzes. Results showed that 2.0 kGy irradiation resulted in a blend with superior antioxidant activity at intermediate times. This treatment also showed the highest increase of vitamin C up to 90 days of storage. The highest levels of Chroma and °Hue were observed at intermediate times in the blend irradiated with 1.5 kGy and at 0 and 120 days with 1.0 kGy. After 120 days, SS content was higher in the blend irradiated with 1.0 kGy and the highest value of total phenolics was observed in the blend irradiated with 1.5 kGy. Sensory tests showed that the sensory quality of the grape juice blends subjected to 2.0 KGy kept unchanged. Gamma irradiation reduced filamentous fungi and yeasts during storage at room temperature.